Pengaruh Kemampuan, Pelatihan dan Komunikasi Kerja Terhadap Kinerja Pegawai pada Kantor Pertanahan Kabupaten Konawe Selatan - Taufik; Kalsum, Ummy; Hakim, Abdul (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyse the influence of competence, training and workplace communication on employee performance at the South Konawe Regency Land Office. The study employs a quantitative approach using a survey method, involving the distribution of questionnaires to 35 employees who served as respondents. The data obtained were analysed using multiple linear regression to test the influence of the variables of competence, training, and workplace communication on employee performance, both simultaneously and partially. The results of the study indicate that competence, training, and workplace communication simultaneously have a positive and significant influence on employee performance. Partially, competence has a positive and significant influence on employee performance, as does training, which makes a positive and significant contribution to improving performance. Furthermore, workplace communication was also found to have a positive and significant effect on employee performance. These findings indicate that improvements in employee performance are strongly influenced by the development of individual skills, the implementation of continuous training, and effective workplace communication within the organisational environment. It is hoped that this study will serve as a basis for consideration by agency leaders in formulating human resource management policies aimed at optimally enhancing employee performance